2013
DOI: 10.1111/acer.12225
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-Motor Deficits in Children with Fetal Alcohol Spectrum Disorder Assessed Using a Robotic Virtual Reality Platform

Abstract: The current study has shown that robotic technology is a sensitive and powerful tool that provides increased specificity regarding the type of motor problems exhibited by children with FASD. The high frequency of motor deficits in children with FASD suggests that interventions aimed at stimulating and/or improving motor development should routinely be considered for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…Deficits in behavior and cognition have long been identified as consequences of ethanol exposure during nervous system development [2, 23, 32, 39, 40, 47, 53, 55, 58, 72]. An estimated 1%-5% of children are diagnosed with fetal alcohol spectrum disorders (FASDs; [41]) which encompass, in decreasing order of severity, full-blown Fetal Alcohol Syndrome (FAS), partial FAS (pFAS), and alcohol-related neurodevelopmental disorders (ARNDs)[12].…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in behavior and cognition have long been identified as consequences of ethanol exposure during nervous system development [2, 23, 32, 39, 40, 47, 53, 55, 58, 72]. An estimated 1%-5% of children are diagnosed with fetal alcohol spectrum disorders (FASDs; [41]) which encompass, in decreasing order of severity, full-blown Fetal Alcohol Syndrome (FAS), partial FAS (pFAS), and alcohol-related neurodevelopmental disorders (ARNDs)[12].…”
Section: Introductionmentioning
confidence: 99%
“…Including measures of balance and motor performance will be necessary in future studies to complement kinematic measures of sensory attention and postural control to examine effects at the levels of both impairment and function. 47 Finally, since this is a feasibility and exploratory study, results are limited by our small sample size and multiple comparisons, and cannot be generalizable without further studies.…”
Section: Immediate Effects: Sensory Attentionmentioning
confidence: 94%
“…Since only the trajectory data near the stimulus frequencies were of interest (ranging from 0.24 to 1.11 Hz), 4 th order Butterworth band pass filter was applied. 47 A Welch smoothing window was applied to avoid spectral leakage, along with a tolerance interval to detect response peaks within 0.02 Hz of the stimulus. To detect phase wrapping, phase (timing of response) was calculated from the timing of the peak cross-correlation of stimulus and response signals and converted to degrees.…”
Section: Data Reductionmentioning
confidence: 99%
“…Researchers have reported that deficits in sensory processing and sensory-motor functioning are related to adaptive behaviour and academic performance in home and school settings among children with FASD [43,44]. Impairments in sensory-motor integration and motor development have been noted in children and youth with FASD, with particularly pronounced difficulties in younger children [45].…”
Section: Sensory-motor Functioning Needsmentioning
confidence: 99%